Efeito do enriquecimento ambiental, associado ou não a atividade física, nas funções nociceptiva, ambulação e controle motor em modelo animal de dor crônica muscular difusa - Dourado, Solano Savio Figueiredo (2015)
Fibromyalgia is a complex syndrome with unknown etiology, characterized by the presence of chronic widespread musculoskeletal pain, having the reduction of the physical/ functional performance as a major comorbidity. Pharmacological treatment of fibromyalgia presents limited effectiveness, making it important to use non-pharmacological therapies, such as physical activity, cognitive behavioral therapy and distracting techniques. The qualification of the environment and the AF has been associated with the treatment of conditions that increase the peripheral and central nociceptive activity. This study proposes the investigation of environmental enrichment (EE), a technique based on physical, sensory and cognitive stimulation, and physical activity (PA) as strategies for fibromyalgia prevention. To this end, 24 male Wistar rats were divided into five intervention groups: 1) EE, 2) PA, 3) EE + PA and 4) control, where they were maintained for 4 weeks. After this time, was diffuse chronic muscle pain induced by two injections of acidic saline in the left gastrocnemius muscle. We evaluated the mechanical paw withdrawal threshold (von Frey electronic), temperature threshold (Hot Plate), neuromuscular activity (Rod Route), ambulation (number of quadrants) through the Open Field in six stages: basal after the 1st, 2nd, 3rd and 4th weeks and 24 hours after induction of diffuse chronic pain model. The animals kept with environmental enrichment and physical activity (EE + PF) showed a significant increase in mechanical and thermal thresholds after the third (P<0.001) and second (P<0002) weeks, respectively, when compared to the other groups. This increase remained at the post-induction assessment, while the other groups showed a significant decrease (P<0.01), suggesting the development of hyperalgesia. In the engine testing, EA + FA group showed a significant increase in neuromuscular activity from the first week compared to the other groups (P<0.01), keeping the increase even after induction, while in the other groups there was a significant decrease in performance (P<0.01), whereas in other groups, there was a significant reduction in weight gain (P<0.01). In the Open Field, a significant increase in the total ambulation in AE + AF group from the 1st week (P<0.01) compared to the other groups. These results suggest an association between environmental enrichment and physical activity as a preventive strategy for chronic musculoskeletal pain and optimization of motor control in a model of diffuse chronic muscle pain.